Victorian Lessons in Empathy and Difference - Mitchell, Rebecca N. (Rebecca Nicole), 1976- (Book collections on Project MUSE., 2011)
"Victorian Lessons in Empathy and Difference amplifies the fundamental distinction between the characters within a text or image--who are intimately unknowable to each other--and the material texts and images--which are eminently knowable to the reader or viewer. To this end, Mitchell's exploration of alterity is grounded in the tradition of Emmanuel Levinas, whose work establishes a vocabulary for considering otherness outside of dialectical oppositions, binaries which so often define recent constructions of Victorian subjectivity. The study turns explicitly from the usual paradigms for encountering Victorian otherness--race, gender, colonized status, or class--to focus instead on the representations of difference where proximity typically precludes the recognition of alterity"--Publisher's description